Perceptions of district residency programme among postgraduate medical students: A cross-sectional study. - Chaithanya, Ejju Krishna; Reddy, Dr Poojitha Ram Vemi; Dr Gali sai Chandana; Dr G. Indrani (Student’s Journal of Health Research Africa, 2025)
Background: The National Medical Commission (NMC) introduced the District Residency Programme (DRP) to strengthen postgraduate medical education through mandatory postings in district hospitals. It aims to enhance clinical exposure, decision-making, and understanding of public health systems while addressing workforce gaps in underserved regions. Objectives: To evaluate postgraduate students’ perceptions of the DRP, focusing on its educational value, challenges, and areas for improvement. Methods: A cross-sectional study was conducted among 217 postgraduate students of Sri Venkateswara Medical College, Tirupati, who had completed DRP postings. Data were collected using a validated questionnaire. Quantitative data were analyzed with descriptive statistics, Chi-square tests, and t-tests; qualitative responses underwent thematic analysis. Results: Most participants were aged 26–30 years (68.5%), with females slightly outnumbering males (53.0% vs. 47.0%). The majority (91.2%) were posted with specialty teams, 88.0% contributed to diagnostic services, and 76.5% reported mentorship. About 67.3% believed DRP would benefit future practice, and 61.8% considered it essential. Areas for improvement included limited access to remote academic activities (44.2% had provision, 55.8% did not) and inconsistent exposure to national health programmes, which several students highlighted as gaps requiring attention. Conclusion: Students valued DRP for clinical exposure, teamwork, and service orientation, but highlighted challenges in academic integration and applicability to non-clinical disciplines. Recommendations: Structured mentorship, digital learning, and specialty-specific models are recommended for sustainability.